Chevaux travaillés et chevaux qui travaillent : réflexions sur la notion de travail dans l’univers équestre - Léa de Boisseuil (In Situ)
Worked horses and working horses, some thoughts on the notion of work in the equestrian world. Looking back over the history of the word ‘work’ in the French language, this paper proposes an enlarged appreciation of the working relationship between men and horses, relationships that cannot be reduced only to productive and working activities. On the contrary, equestrian activities generate a variety of relationships, aimed at elaboration and improvement, two fundamental aspects of work. The historical and social status of the concept of work gives a deep cultural and identity character to the heritage of the ‘workhorse’.